Nursing intervention in neonatal metabolic screening: Integrative review - Salmón Vega, Silvia Guadalupe (Universidad de Sonora, 2022)
Introduction: Neonatal metabolic screening refers to a group of procedures and tests performed in order to separate among apparently healthy newborns, those with suspected inborn errors of metabolism. Therefore, it allows detecting the disease before it appears and initiating the treatment in time in order to prevent complications, disability and death. Currently, the neonatal metabolic screening is decisive for reliable results. Objective: Conduct an integrative literature review of nursing intervention in neonatal metabolic screening. Methodology: Integrative research in the databases Web of Science, Scielo, Scopus, Pubmed, Sciencedirect, Dialnet, OVID and EBSCO, using the descriptors neonatal screening, nursing care, inborn errors of metabolism, neonatology and analgesia; with the Boolean operators and, or and not. Of 116 documents obtained, 36 met eligibility criteria and represent the study material. Results: Blood sample collection for screening was performed between the third and fifth day of life, essentially by capillary puncture of the heel. Non-pharmacological analgesic measures are breastfeeding, kangaroo method and containment. The sample shall be protected from contamination, and its stability depends on the storage temperature until analysis is performed. Conclusions: The scientific literature reviewed empowers the nursing professional to provide comprehensive and safe care to the newborn who participates in the program.